Manufacturing and Characterization of Three Modified Vegetable Oil-Added Polylactic Acid Composites - Sen, Ibrahim; Atagur, Metehan; Tuna, Sibel; Eroglu, Murat; Kurtlu, Meral Akkoyun; Sever, Kutlay (Wiley, 2024)
Polylactic acid (PLA) was modified with three types of modified vegetable oils (MVOs), which are the epoxidized soybean oil (ESBO), maleinized sunflower oil (MSO), and maleinized olive oil (MOO), at different weight fractions. A corotating twin screw extruder was used to produce composite materials by the melt-mixing process. The effect of MVO content, from 2.5% to 10%, on the morphology, mechanical properties, density, and water absorption was investigated in detail. The addition of ESBO and maleinized vegetable oils leads to a slight decrease in the density of PLA from 1.252 to 1.231 g/cm3. As the concentration of MVO in PLA increases, the amount of water absorption also increases, and the highest water absorption value was observed in P10MSO. The FTIR spectra of all concentrations of the MOO and MSO have two peaks at 1781 and 1861 cm-1, attributed to the C=O stretching which is related to maleic acid copolymerization. In general, the elastic modulus (EM) was slightly changed by the addition of MVOs to PLA, while the tensile strength (TS) decreased. Due to the plasticizing effect of MVOs, an increase in the Izod impact strength was obtained.
Keywords: maleinization; mechanical properties; modified vegetable oils (MVO); polylactic acid (PLA)